Impact of extreme wildfires on the geotechnical properties of volcanic soils: A specific dataset from Central-Southern Chile(Zenodo). - Eduardo Javier Paredes-Delgado; Ignacio Pérez-Rey; Juan López-Vinielles; Roberto Tomás; Mauro Muñiz-Menéndez; Pablo Miranda; Roberto Sarro (Data in Brief, 2025)
The increasing occurrence of wildfires, driven by climate change and environmental degradation, highlights the importance of studying their effects from the perspective of geotechnics and soil mechanics. During a wildfire in 2023 in Central-Southern Chile, temperatures in eucalyptus forests reached up to 600 °C, resulting in significant physical and chemical alterations in the soil. This dataset focuses on the impact of wildfires on the geomechanical properties of volcanic soils in central Chile, providing data collected through laboratory tests and in-situ survey techniques. The methods employed include: (i) delineation of areas severely affected by the 2023 wildfires in the Biobío region of Chile; (ii) measurement of soil geomechanical parameters in affected areas and comparison with pre-fire values; and (iii) compilation of a dataset to facilitate the evaluation of post-fire changes in soil geomechanical properties. This dataset can serve as a reference for assessing the impacts of wildfire-induced changes in soils, providing valuable insights for identifying areas prone to ground instability and informing civil engineering projects.